Comparisons of front plate, percutaneous sacroiliac screws, and sacroiliac anterior papilionaceous plate in fixation of unstable pelvic fractures. Issue 36 (September 2017) - Gu, Ronghe; Huang, Weiguo; Yang, Lijing; Liu, Huijiang; Xie, Kegong; Huang, Zonggui
Abstract: Background: This observational study was aimed at comparing the clinical efficacy of sacroiliac anterior plate fixation (SAPF), sacroiliac anterior papilionaceous plate (SAPP), and percutaneous sacroiliac screw internal fixation (PSCIF) introduced for patients with unstable pelvic fracture. Methods: Seventy-eight patients with unstable pelvic fracture (Tile type B or C) were recruited. Twenty-six patients underwent SAPF, 26 underwent SAPP, and 26 underwent PSCIF. Matta scores were calculated to evaluate the reduction of pelvic fractures, and Majeed scores were applied for the assessment of functional recoveries after surgery. Other perioperative clinical indicators were also recorded, including operation time, bleeding status, length of incision, ambulation time, fracture healing time, and incision infection. Results: Total operation time of PSCIF was remarkably shorter than that of SAPF and SAPP ( P < .05), and the bleeding volume of SAPF and SAPP group was almost 26∼29 times as high as that of PSCIF group ( P < .05). Besides, SAPP resulted in significant blood loss compared with SAPF ( P < .05), while SAPF resulted in significantly larger operative incision length than SAPP and PSCIF ( P < .05). Moreover, patients' stay time was prolonged in both SAPF and SAPP groups than in the PSCIF group ( P < .05). Patients who received PSCIF exhibited significantly higher Matta and Majeed scores than those who received SAPF (all P < .05). Finally, SAPP was associated with fewer complications than SAPF, and complications were barely observed in the PSCIF group. Conclusion: PSCIF may be more appropriate for patients with unstable pelvic fractures in comparison with SAPP and SAPF. Besides, SAPP is likely to be more efficacious than SAPF especially for Tile C patients. Abstract : Supplemental Digital Content is available in the text